DOZ047.35: Early parental adjustment in esophageal atresia and other rare abdominothoracic malformations. (24th June 2019) - Ribeiro, M-H; Hanafi, M; Michaud, L; Blanc, S; Lapillonne, A; Mur, S; Gelas, T; Kermorvant, E; Gottrand, F; Guerrien, A; Coulon, N
Abstract: Parents of a child with a congenital malformation including esophageal atresia (OA), congenital diaphragmatic hernia (CDH), or intestinal atresia (IA) have to face various potentially stressful situations and exercise their role in a highly medicalized context. Yet no study has so far sought to identify the factors that facilitate or make difficult their adjustment of the first months. This study aimed to propose a grounded theory to account for the dynamics of parental adjustment for the period from the announcement of the diagnosis to the age of one year of the child with a rare abdominothoracic malformation requiring neonatal surgery. Participants were recruited to form a reasoned sample of 30 parents of children aged from 12 to 36 months with an OA, a CDH, or an IA. To date, 22 parents (17 mothers and 5 fathers) have been included. Semistructured individual interviews were conducted in which four main themes were discussed: the medical and hospital care of the child, the daily life with the child at home, the consequences of the illness on family life, and personal experience. Preliminary results show that the child's condition impact parental adjustment and family functioning. Parents reported high level of distress and fatigue during the first year of their child. The highly medicalized context makes it more difficult for parents to practice their parental role and bring them to expense energy to implement normalization strategies in their parental practices. Interestingly, the relationship with doctors and medical staff has been widely discussed by parents. Most of them felt a lack of information about their child's condition, or felt that the information was not authentic. Some of them felt that doctors were trying to protect them by omitting certain events that they ended up learning by the medical staff. All parents pointed the availability, the quality of the educational relationship, the emotional and informational support from the medical staff allowing them to feel more effective and to reduce their negative feelings. Results of our study will be used to design appropriate psychoeducational interventions in order to improve support for families.